1985
DOI: 10.1159/000238368
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ceftazidime in Patients with Renal Insufficiency and in Those Undergoing Hemodialysis

Abstract: The pharmacokinetics of ceftazidime, a new cephalosporin antibiotic, were studied in 7 healthy volunteers and 32 patients with renal insufficiency after a single 500-mg intravenous injection. The mean plasma half-life during β-phase was 1.67 h in normal subjects and was prolonged to 15.09 h in hemodialysis patients. There were significant correlations between the elimination rate constant and the creatinine clearance, and between the β-phase rate constant and the creatinine clearance. The mean urinary recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…The predicted Vss (0.20 L/kg) is consistent with the reported data from Leroy's, Welage's and Ohkawa's studies, but lower than the reported values from van Dalen's and Lin's studies (Table ), even though the AUCs of the two studies were not significantly different from others considering the high variability (Table and Figure ). According to the authors' interpretations, combination of factors including extensive bed rest, severe hypoalbuminaemia, fluid retention, ratio of lean body mass to total body‐weight, etc could be responsible for the increased distribution volume observed in those intensive care patients and patients with infectious diseases .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The predicted Vss (0.20 L/kg) is consistent with the reported data from Leroy's, Welage's and Ohkawa's studies, but lower than the reported values from van Dalen's and Lin's studies (Table ), even though the AUCs of the two studies were not significantly different from others considering the high variability (Table and Figure ). According to the authors' interpretations, combination of factors including extensive bed rest, severe hypoalbuminaemia, fluid retention, ratio of lean body mass to total body‐weight, etc could be responsible for the increased distribution volume observed in those intensive care patients and patients with infectious diseases .…”
Section: Discussionsupporting
confidence: 88%
“…The AUC values from the five reported trials were consistent in each renal function group. The predicted AUC inf values in normal, mild and moderate groups were 138.5 ± 19.6, 230.7 ± 22.2 and 369.3 ± 53.1 h µg/mL (mean ± SD), respectively, in close agreement with the weighted mean AUC of the five reported clinical studies, 139.4 ± 30.8, 242.7 ± 70.8 and 381.7 ± 116.4 h µg/mL (mean ± SD), respectively . Considering both Cockcroft‐Gault and Modification of Diet in Renal Disease (MDRD) methods were used for GFR characterization in the clinical studies, subjects were simulated using both methods.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The tl;' of ceftriaxone does not change appreciably in the presence of moderate renal impairment and increases only moderately in severe renal dysfunc- Table II. Serum half-lives (tv,) and recommended dosaged adjustment in renal impairment (data from Barbhaiya et al 1990b: Brown_ ing et al 1986Conte 1987;Guay et al 1986;Halstenson et al 1990;Kneer et al 1989;Konishi 1986;Konishi & Ozawa 1984: Lecaillon et al 1984Leroy et al 1981;Matzke et al 1985;Ohkawa et al 1985Ohkawa et al ,1989Polk et al 1984;Van Dalen et al 1986: Wise et al 1981Yuk et al 1989 a The t'n of desacetyl-cefotaxime is 5.65h in patients with CLcR of 10 to 30 mlfmin (0.6 to 1.8 LfL) and 10h in those with CLCR of < 10 mlfmin (0.6 Lfh). Abbreviations: HD = haemodialysis; PD = peritoneal dialysis; CAPD = continuous ambulatory peritoneal dialysis; NC = no change; qxh = every x hours.…”
Section: Renal Impairmentmentioning
confidence: 99%